Determinant factors on natural regeneration in a fragment of araucaria forest on Santa Catarina State plateau Fatores determinantes da regeneração natural em um fragmento de floresta com araucária no planalto catarinense - Buzzi F.* (2015)
This study aimed to describe the floristic and regenerative component structure in an Araucaria Forest fragment and to evaluate the influence of environmental variables and adult tree component (DBH ≥ 5 cm) on natural regeneration spatial organization. In 50 sampling units, botanic identification and the height class (h) were recorded for all regenerative individuals: Class 1 (20 cm ≤ h ≤ 1 m), Class 2 (1 < h ≤ 3 m), Class 3 (h > 3 m e DBH < 5 cm). In addition, in each plot, variables related to soil, terrain, canopy cover, density and richness of trees with DBH ≥ 5 cm were recorded. The relation between the regenerative component and the variables were analyzed by a Canonical Correspondence Analysis (CCA). The survey totaled 79 regenerative species. The richest family was Myrtaceae with 20 species. The results showed a sharp reduction in abundance from the smaller to the larger size class and little influence of the analyzed variables on regenerative component spatial organization.